MANAJEMEN RESIKO PADA PENGUJIAN ROV DI PT. SAMUDERA OCEANEERING - Sadiq Ardo Wibowo; citra indah asmarawati; Chandra Putra (JURNAL REKAYASA SISTEM INDUSTRI, 2022)
PT. Samudera Oceaneering is a branch of Oceaneering International Incorporated with main focus on the oil and gas industry. As a branch company of ROV, PT. Samudera Oceaneering always ensures that the ROV that will be sent for underwater works is in top notch condition and has been tested prior to the project to ensure all the functions are working properly and meet the specifications set by the client. In this internship the author takes a specific topic of risk management on ROV testing at PT. Samudera Oceaneering. Hazard identification is carried out in detail on the ROV testing process using the JSEA method. The risk assessment in the ROV testing process was obtained with the majority of the testing process being at high risk level. Based on the results of the risk assessment, the recommendation for risk control on the potential hazards that exist including installing a barricade in the test area, using the right PPE and tooling that is in good condition, ensuring that each item used has passed the test and is certified.